Strategy for Utilizing Online Discussions and Online Practices on SPADA LMS to Improve Physics Learning in the Digital Era - Iryani, Juniarti; Syam, Nurwahid (Universitas Muhammadiyah Makassar, 2024)
The rapid development of digital learning platforms, particularly Learning Management Systems (LMS) such as SPADA, has significantly transformed physics education by enabling interactive and flexible learning environments. However, the effectiveness of integrating online discussions and exercises in enhancing students' comprehension of physics concepts remains underexplored. This study aimed to evaluate the impact of online discussions and exercises conducted through the SPADA LMS on students' understanding of physics concepts. A quantitative approach with a one-group pre-test and post-test experimental design was employed, involving 18 students enrolled in a physics course. Data were collected using questionnaires, pre-tests, post-tests, and interviews. The results revealed a substantial improvement in students' comprehension, with the average post-test score (75.18) significantly exceeding the pre-test score (47.75). Students reported increased engagement, better conceptual understanding, and improved problem-solving skills through active participation in online discussions and structured exercises. However, challenges such as technical issues, including unstable internet connectivity, occasionally disrupted participation. Despite these obstacles, the integration of online discussions and exercises through SPADA LMS proved to be an effective strategy for enhancing students' comprehension of physics concepts and fostering a collaborative learning environment. This study highlights the potential of LMS platforms as essential tools for advancing digital education, with implications for improving instructional design and promoting interactive learning experiences in physics education. Future research should explore the integration of multimedia tools and adaptive learning features to further optimize LMS-based instruction in physics.